Do IgA antigliadin and IgA antiendomysium antibodies show there is latent coeliac disease in primary IgA nephropathy?. Issue 4 (April 1992) - Sategna-Guidetti, C; Ferfoglia, G; Bruno, M; Pulitano, R; Roccatello, D; Amore, A; Coppo, R
Abstract : The finding in primary IgA nephropathy of increased levels of IgA to food antigens and particularly to gliadin prompted the hypothesis that a subgroup of these patients may have latent coeliac disease. The observation that gliadin may experimentally induce IgA mesangial deposits supported this hypothesis. We evaluated specific immunological markers of coeliac disease (antiendomysium antibodies) which parallel histological changes of gluten sensitive enteropathy, and an IgA immunofluorescent test for antigliadin antibodies in 18 patients with IgA nephropathy, in 56 untreated coeliac disease patients, in 254 controls (58 healthy and 196 disease controls). Antiendomysium antibodies were positive in 89.28% of coeliac patients, but negative in all IgA nephropathies and controls. IgA immunofluorescent test for antigliadin antibodies, negative in all IgA nephropathy patients, was positive in 76.78% of coeliac patients and in 4.91% of controls. ELISA IgA antigliadin antibodies were negative in controls, but positive in 22.22% of IgA nephropathy patients and in 60.71% of coeliac patients. Our data would suggest that in most patients with IgA nephropathy there is no evidence of latent coeliac disease.